Self-Perception of Giftedness in Adolescents Selected for Gifted Education Programmes - Volkova, E.N.; Miklyaeva, A.V.; Kosheleva, A.N.; Khoroshikh, V.V. (Psihologičeskaâ nauka i obrazovanie, 2020)
Specialized support for gifted children and adolescents should be based on the specifics of their social situation of development which is largely determined by the fact of identifying a person as gifted. ‘Labeling giftedness’ has a significant impact on the system of interpersonal relationships and self-attitude of children and adolescents. However, there is no holistic construct of the phenomenon of ‘self-perception of giftedness’ in psychology today, therefore, we defined the theoretical and empirical development of this construct as the goal of our study. The paper presents the results of this study which describes the construct of ‘self-perception of giftedness’ basing on the survey of 422 adolescents aged 15—17 years who had been selected for gifted education programmes. Using factor analysis we identify the main dimensions of the construct typical for late adolescence: giftedness resources/risks assessment; environment of risks and resources manifestation (internal/external); localization of conditions for high achievement (internal — external).Basing on the analysis of the significance of differences, we outline the perspectives of using the construct to reveal gender specifics of self-perception of giftedness in older adolescents enrolled in gifted education programmes. Представлены результаты исследования, в котором на основании результатов анкетирования 422 подростков 15—17 лет, прошедших педагогический отбор на специализированные образовательные программы, был описан конструкт «отношение к собственной одаренности». Авторы исходят из того, что специализированная поддержка детей и подростков с признаками одаренности предполагает учет особенностей их социальной ситуации развития, в значительной мере определяемой фактом идентификации личности в качестве одаренной. «Маркировка одаренности» оказывает существенное влияние на систему межличностных отношений, а также самоотношение детей и подростков. Однако на сегодняшний день в психологии отсутствует целостный конструкт феномена «отношение к собственной одаренности», что определило теоретическую и эмпирическую разработку конструкта отношения к собственной одаренности в качестве цели представляемого в данной статье исследования. С помощью факторного анализа были выделены основные размерности конструкта «отношение к собственной одаренности», типичные для старших подростков: оценка ресурсов — рисков одаренности; среда проявления рисков и ресурсов одаренности (внутренняя — внешняя); локализация условий высоких достижений (внутренняя — внешняя). На основе анализа достоверности различий показаны возможности конструкта для выявления половой специфики отношения к собственной одаренности у старших подростков, обучающихся по специализированным образовательным программам.